Novel integrative options for passive filter inductor in high speed AC drives - Raza Khowja, M.; Gerada, C.; Vakil, Gaurang; Wheeler, Patrick; Patel, Chintanbai (2016)
This paper presents novel integration options for passive inductor which include: motor-shaped rotational and motor-shaped rotor-less inductor for high speed motor drive system. The novel options have been designed and their performance is compared with the conventional EE core inductor using finite element analysis. It is observed that there is a significant reduction in total losses at fundamental frequency along with substantial reduction in the AC copper loss at 10, 15 and 20 kHz switching frequencies, when the proposed integrated options are utilized. For the motor-shaped rotational inductor, the total losses at fundamental frequency and AC copper loss at different switching frequencies are reduced by 26.1% and 73.8% (at different switching frequencies) respectively. There is a reduction in overall volume by 3.6%, but this comes with 11.7% increase in weight. For the motor-shaped rotor-less inductor, the total losses at fundamental frequency and AC copper loss at different switching frequencies are reduced by 10.4% and 73.8% (at different switching frequencies) respectively. There is a reduction in overall volume by 3.6% but this comes with 6.1% increase in weight. The proposed designs can share the cooling system of the motor thus, eliminating the requirement of separate cooling system.